2019
DOI: 10.1111/jhn.12662
|View full text |Cite
|
Sign up to set email alerts
|

Malnourished adults’ receipt of hospital discharge nutrition care instructions: a pilot study

Abstract: Background Malnutrition remains an important yet under‐recognised problem among hospitalised adults. Although interventions exist aiming to improve nutritional status beyond hospitalisation, few studies examine how often and what type of nutrition care instructions are given at discharge. The present study sought to review nutrition‐focused discharge care provided to malnourished adults. Methods We reviewed the electronic medical record for discharge nutrition care instructions provided to adult patients ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…This highlights the need to reach vulnerable groups in the community and to be able to identify issues before they develop. This would include: practical ways of measuring nutritional status and body composition validated against criterion measurements ; improvements in communication after discharge ; and adaptation of the current screening methods according to the circumstances . Improvements in this area have already been made with novel developments in self‐screening tools that are more suitable for community use in the voluntary sector domiciliary care and with social care partners.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to reach vulnerable groups in the community and to be able to identify issues before they develop. This would include: practical ways of measuring nutritional status and body composition validated against criterion measurements ; improvements in communication after discharge ; and adaptation of the current screening methods according to the circumstances . Improvements in this area have already been made with novel developments in self‐screening tools that are more suitable for community use in the voluntary sector domiciliary care and with social care partners.…”
Section: Discussionmentioning
confidence: 99%
“…94 Further, nutrition recommendations at discharge were often inadequate. 93 Adherence to dietitian-prescribed ONS after discharge was lower than when prescribed by the primary care physician. 96 It was suggested that transition care models could improve continuation of malnutrition care into the community.…”
Section: Transitions and Postdischarge Nutrition Carementioning
confidence: 95%
“…Fifteen articles, [70][71][72][86][87][88][89][90][91][92][93][94][95][96][97] including 2 systematic reviews, 86,87 5 RCTs, [70][71][72]88,89 and 3 non-RCT interventions, [90][91][92] focused on postdischarge nutrition care. It was found that dietitian consults after discharge were rare, 95 despite a quarter of medical and surgical patients showing continued weight loss after return to the community.…”
Section: Transitions and Postdischarge Nutrition Carementioning
confidence: 99%
See 1 more Smart Citation
“…Research also confirms that the majority of malnourished adult patients receive inappropriate or inadequate nutrition care instructions at the time of discharge. In adult patients identified by dietitians as being malnourished, records show that only 6.6% received discharge instructions to consume oral nutrition supplements while almost half (47.4%) received general diet instructions that did not address malnutrition and 44.8% received inappropriate instructions to limit caloric intake (Brooks et al, 2019).…”
Section: Providing Adequate Nutrition Care Instructionsmentioning
confidence: 99%